Suppression of store-operated Ca2+ entry regulated by silencing Orai1 inhibits C6 glioma cell motility via decreasing Pyk2 activity and promoting focal adhesion. Issue 24 (16th December 2020) - Zhu, Meng; Lv, Bingke; Ge, Wenjing; Cui, Zhenwen; Zhao, Kai; Feng, Yugong; Yang, Xuejun
ABSTRACT: Store-operated Ca 2+ entry (SOCE) plays an important role in regulating Ca 2+ influx, which participates in tumor cell survival and motility. We aim to elucidate the role of SOCE in the behavior of C6 glioma cells. Lentiviral vector inserted with the Orai1-targeting shRNA was used to inhibit SOCE in C6 glioma cells. The down-regulation of Orai1 was confirmed by western blot. The ability of shOrai1 or SOCE inhibitor (SKF96365) in regulating SOCE inhibition was evaluated by measuring Ca 2+ concentration. Additionally, its effect on cell behavior was assessed using methyl thiazolyl tetrazolium (MTT) assay, wound healing assay, transwell assay, and adhesion assay. Focal adhesions were visualized by immunofluorescence assay. Further, the expression of proline-rich tyrosine kinase 2 (Pyk2) and phosphorylated Pyk2 (p-Pyk2) was analyzed using western blot. Both, SKF96365 treatment and the Orai1 down-regulation inhibited SOCE by perturbing Ca 2+ influx. The inhibitory effects of shOrai1 on C6 cell proliferation, migration, and invasion were similar to that of SKF96365. Moreover, Orai1 inhibition enhanced C6 cell adhesion by increasing the size of focal adhesion plaques. The down-regulation of Pyk2 was observed in both SKF96365-treated and Orai1-silenced C6 cells. Additionally, Orai1 inhibition blocked AKT/mTOR, NFAT, and NF-κB pathways. The silencing of Orai1 inhibited the C6 glioma cell migration, invasion and contributed to focal adhesion.